Eminent economists II : their life and work philosophies - Szenberg, Michael; Ramrattan, Lall, 1951- (Cambridge : Cambridge University Press, 2014)
The sequel to Eminent Economists, this book presents the ideas of some of the most outstanding economists of the past half century. The contributors, representing divergent points of the ideological compass, present their life philosophies and reflect on their conceptions of human nature, society, justice, and the source of creative impulse. These self-portraits reveal details of the economists' personal and professional lives that capture the significance of the total person. The essays represent streams of thought that lead to the vast ocean of economics, where gems of the discipline lie, and the volume will appeal to a wide array of readers, including professional economists, students and laypersons who seek a window into the heart of this complex field. The contributors include Alan S. Blinder, Clair Brown, John Y. Campbell, Vincent P. Crawford, Paul Davidson, Angus Deaton, Harold Demsetz, Peter Diamond, Avinash Dixit, Barry Eichengreen, Jeffrey Frankel, Richard B. Freeman, Benjamin M. Friedman and John Hull.
Foreword / by Robert Solow -- Introduction / Michael Szenberg and Lall B. Ramrattan -- Being there: an intellectual journey / Alan S. Blinder -- Social norms in economics and in the economics profession / Clair Brown -- Personal reflections on my professional life / John Y. Campbell -- Gray eminence? / Vincent P. Crawford -- Biochemist to economist / Paul Davidson -- Puzzles and paradoxes: a life in applied economics / Angus Deaton -- Succeeding in economics / Harold Demsetz -- My research strategy / Peter Diamond -- My philosophy of economics, life, and everything (not!) / Avinash Dixit -- Finding a niche / Barry Eichengreen -- Become an economist -- see the world / Jeffrey Frankel -- Practitioner of the dismal science? Who, me? Couldn't be!! / Richard B. Freeman -- One job, four careers / Benjamin M. Friedman -- My life and research strategy / John Hull -- How I ended up being a multifaceted economist and the mentors I have had / Michael D. Intriligator -- Searching for my personal philosophy / Peter B. Kenen -- Learning about the evolving international economy / Anne O. Krueger -- Confessions of a Wellesley FEM / Helen F. Ladd -- God, ants, and Thomas Bayes / Harry M. Markowitz -- The path of a monetary economist / Frederic S. Mishkin -- Learning from the field / Elinor Ostrom -- Order in and through disorder: the invisible hand as a turbulent regulator / Anwar Shaikh -- The education of an economist / Jeremy J. Siegel -- Faith, science, and religion / Vernon L. Smith -- My studies in international economics / Robert M. Stern -- Sailing into the wind / Myra H. Strober -- My life and work philosophy / Hal R. Varian -- Scaling fortress economics / Michelle J. White -- The accidental economist / Marina v. N. Whitman.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Economists -- Biography; Economics -- Philosophy